Effects of partial silage replacement with corn stover pellets on the rumen microbiota and serum metabolome of breeding cows - Jiao, Chenyue; Cui, Changze; Qi, Youpeng; Zhang, Meixian; Zhao, Pengcheng; Chen, Shaopeng; Wang, Xiangyan; Hu, Jiang; Shi, Bingang; Liu, Ting; Zhao, Zhidong; Zhao, Fangfang (Frontiers in Microbiology, 2025)
IntroductionStraw pellet ration replacing part of silage is of great significance for farmers to save farming costs and solve the lack of feed resources. A comprehensive analysis of rumen microbial and serum metabolite compositions is conducted to promote the development of the modern breeding cows-feeding industry.MethodsIn this study, 18 healthy 2-year-old Simmental breeding cows weighing 550 ± 20 kg were selected and randomly divided into two groups. They were fed under the same feeding conditions for 70 days, of which 8 in the control (CON) group were fed 65% roughage (100% silage) + 35% concentrate, and 10 in the treatment (TRT) group were fed 65% roughage (50% corn stover pellets +50% silage) + 35% concentrate, and milk quality, serum immunity indexes, serum metabolomes, rumen fermentation parameters, rumen Microorganisms.ResultsThe results showed that there was no significant difference in production performance between the two groups of breeding cows fed hay and Corn stover pellet feed (p < 0.05); Immunoglobulin A (IgA) was significantly higher in TRT compared to CON (p < 0.05), and there was no significant difference in Immunoglobulin G (IgG) and Immunoglobulin M (IgM) between the two groups (p > 0.05); a total of 92 differential metabolites were screened out in the serum metabolomics analysis, among them, L-valine, L-leucine, L-arginine, L-cysteine, L-tyrosine, and L-tryptophan were up-regulated; In rumen fermentation parameters there was no significant difference between CON and TRT in rumen pH, rumen ammonia nitrogen (NH3-N) content, rumen Acetic/Propionic concentration (p > 0.05), and the concentration of Acetic, Propionic, butyric and Total volatile fatty acids (TVFA) in CON was significantly lower than that in TRT (p < 0.05). Among the rumen microorganisms, the dominant groups were Thick-walled Firmicutes, Bacteroidota, Prevotella and Ruminalococcus. In the correlation analysis between rumen fermentation parameters and rumen microorganisms, Propionic and TVFA showed a significant positive correlation with Prevotella (p < 0.05), butyric showed a highly significant positive correlation with Prevotella (p < 0.01), and propionic butyric, and TVFA showed a positive correlation with Bacteroides (p < 0.05); L-cysteine was significantly positively correlated with Prevotella and Anaeroplasma (p < 0.05) and Eubaterium in rumen microbial-serum metabolite correlation analysis (p < 0.01).ConclusionThe microbial and metabolomic analyses provide us with essential data support to further provide a scientific basis for breeding cows feeding through the feeding pattern of straw pellets instead of silage, which will help breeding cows farming in future research.